Lessons Learned from Initial Piloting of Farmer-Orientated Value Chain Training in the Pacific - Francis, Judith Ann; Shepherd, A.; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2017)
There have been numerous initiatives in the Pacific region over the past decade to mainstream the concept of value chains into the agricultural development arena.